Trajectories of socioeconomic inequalities in health, behaviours and academic achievement across childhood and adolescence - Howe, Laura D (BMJ Publishing Group, 2013)
BACKGROUND: Socioeconomic inequalities are a key policy challenge. Studies to date have not taken a unified approach to assess how socioeconomic inequalities in health, behaviour and educational attainment change as children age. METHODS: We examined maternal education inequalities in multiple offspring health, behavioural and educational outcomes and how these changed across childhood and adolescence in the Avon Longitudinal Study of Parents and Children, a cohort born in 1991/1992 in South-West England (N=5560–11 463). RESULTS: Inequalities were observed for some health measures (blood pressure (BP), height, cholesterol, bone mineral density (BMD) and fat-mass (females)) but not in other measures (parent-assessed child health, triglycerides, fat-mass (males), high-density lipoprotein-cholesterol, C reactive protein). The strongest health inequality was systolic BP (mean difference comparing highest to lowest maternal education −0.28 SD (95% CI −0.35 to −0.20), approximately 2.6 mm Hg. Wide inequalities, similar in magnitude to BP, were observed for behavioural outcomes. Even greater inequalities were observed for offspring academic achievement (mean difference comparing highest to lowest maternal education 1.43 SD (95% CI 1.37 to 1.50), a difference of 22%). For all behavioural outcomes and some health indicators, inequality was stable over childhood. For some outcomes (BP, BMD and most education outcomes), inequality narrowed as children got older. Only for height and attainment in English tests was there evidence of widening inequalities with age. CONCLUSIONS: Our results suggest that within this cohort, maternal education inequalities in offspring health, behaviour and educational attainment are established in childhood but do not increase up to adolescence. Maternal education inequalities in behaviour and educational attainment were considerably larger than in health measures.